98.2k views
7 votes
-4x+9y=9
x-3y=-6
Solve using Elimination

User Kamal Lama
by
4.4k points

1 Answer

11 votes

Answer:

Explanation:

Multiply the first equation by 4,and multiply the second equation by 1.

4(x−3y=−6)

1(−4x+9y=9)

Becomes:

4x−12y=−24

−4x+9y=9

Add these equations to eliminate x:

−3y=−15

Then solve−3y=−15for y:

−3y=−15 (Divide both sides by -3)

y=5

Now that we've found y let's plug it back in to solve for x.

Write down an original equation:

x−3y=−6

Substitute5foryinx−3y=−6:

x−(3)(5)=−6

x−15=−6(Simplify both sides of the equation)

x−15+15=−6+15(Add 15 to both sides)

x=9

User Nizar
by
5.1k points